THU0203 REAL WORLD EFFECTIVENESS OF BARICITINIB IN THE SWISS RHEUMATOID ARTHRITIS REGISTER (SCQM-RA). (2nd June 2020) - Gilbert, B.; Lauper, K.; Courvoisier, D.; Perrier, C.; Muller, R.; Finckh, A.
Abstract : Background: Patients with rheumatoid arthritis (RA) intolerant or not responding adequately to conventional synthetic DMARD (csDMARD) usually receive biological DMARDs (bDMARDs) or targeted synthetic DMARDs (tsDMARDs) as 2 nd line. Baricitinib (BARI), a once-daily oral selective Janus kinase inhibitor, is efficient in randomised controlled trials but still lacks evidence for effectiveness in real world settings. Objectives: To characterise patients initiating treatment with BARI or other alternative bDMARDs, and to perform an analysis of drug maintenance. Methods: This is an observational, prospective, cohort study, within the Swiss Clinical Quality Management (SCQM) register. All treatment courses (TC) initiated between 2017-09-01 and 2019-10-01 were considered, comparing TC with BARI (BARI group) to TC with alternative bDMARDs, either TNF inhibitors (TNFi group) or other mode of action bDMARDs (OMA group), excluding rituximab. Baseline characteristics were compared using ANOVA or χ2 tests. The crude drug maintenance was assessed by survival analysis (Kaplan-Meier). To correct for potential confounding factors, a Cox proportional hazard model was used. Missing values were imputed using multiple imputation with chained equations. Results: During the study period, 979 TC were initiated (240 in BARI group, 461 in TNFi group and 278 in OMA group). BARI was prescribed to significantly older patients, with longer disease durations and more previous treatment failures (Table 1 ). Unadjusted drug maintenance was significantly shorter in the TNFi compared to the BARI group (log rank p = 0.019). After adjustment for potential confounding factors, the hazard of TNFi discontinuation remained higher than for BARI (Hazard Ratio (HR) 1.48 (95% CI = [1.05 – 2.09]; p = 0.02)). A similar trend was observed when comparing the OMA drugs to BARI, with a HR for discontinuation of 1.42 (95% CI = [0.98 – 2.05]; p = 0.06) (Figure 2 ). Covariates significantly associated with decreased drug maintenance were concomitant csDMARD and concomitant glucocorticoids (Figure 2 ). Conclusion: In this preliminary analysis, baricitinib was prescribed to older patients, with longer disease durations, and more previous treatment failures compared to alternative bDMARDs. Baricitinib demonstrated a significantly higher drug maintenance than TNFi, while similar trend was observed in comparison to OMA drugs. Conflict of interest: This analysis has been made possible by financial support of Eli Lilly (Suisse) SA to the Geneva University Hospitals (HUG). Disclosure of Interests: Benoit GILBERT: None declared, Kim Lauper: None declared, Delphine Courvoisier: None declared, Clementine Perrier Shareholder of: Share of Eli Lilly Company, Employee of: I am currently an employee of Eli Lilly Suisse SA, Rudiger Muller Consultant of: AbbVie, Nordic, Sandoz, Axel Finckh Grant/research support from: Pfizer: Unrestricted research grant, Eli-Lilly: Unrestricted research grant, Consultant of: Sanofi, AB2BIO, Abbvie, Pfizer, MSD, Speakers bureau: Sanofi, Pfizer, Roche, Thermo Fisher Scientific